Dirofilaria repens in a Pediatric Patient—First Case Report from Switzerland - Rose, Rebekka; Kleitsch, Kai-Uwe; Born, Diana; Heye, Pascal (European Journal of Pediatric Surgery Reports, 2023)
We report the first case of Dirofilaria repens in a 4-year-old male patient in Switzerland. The disease is a vector-borne parasitic infection that is not endemic to Switzerland. A 4-year-old male presented with a tender mass in the left groin. The patient was taken to the operating room for surgical exploration to rule out a pathology that could be harmful to the spermatic cord. A node was found along the spermatic cord and excised. Histopathology and microbiology studies revealed the diagnosis of Dirofilaria repens.Even though Switzerland is not endemic to Dirofilaria repens, the diagnosis of a parasitic infection should be considered in patients presenting with subcutaneous nodules in correlation with a travel history to endemic areas. The treatment consists of complete excision of the affected tissue.
Keywords: Dirofilaria; D. repens; spermatic cord; testis; scrotum